Adjacency Pairs in ‘Daebak Show’ YouTube Video: Conversation Analysis - Hero Gunawan; Amelia Latifah (Universitas Veteran Bangun Nusantara, 2023)
The research is intended to analyse the adjacency pair in the video conversation between Eric Nam and Jackson Wang. The purpose of this research is (1) to identify the conversation pattern between Eric Nam and Jackson Wang and (2) to analyse the types of responses based on the adjacency pairs pattern that occurs in the conversation between Eric Nam and Jackson Wang. The data source used is a YouTube video published by Dive Studio which contains a conversation between Eric Nam and Jackson Wang in Daebak Show season 2, episode 5 part 1. The method used to conduct this research is descriptive-qualitative. The theoretical bases of this research is Levinson’s theory (1983) and Schegloff’s theory (2007). The result of this research shows that (1) 106 adjacency pair pattern data have been identified with the number of frequencies of each pattern as follows: 56 Question-answer/Unanswered, 28 Assessment-Agreement/Disagreement, 8 Request-Acceptance/Refusal, 7 Offer/Invite-Acceptance/Refusal, and 7 Blame-Denial/Admission. (2) Based on each pattern found, analyzed the type of response and found 80 (75%) data belonging to the preferred response type and 26 (25%) data belonging to the disreferred response. The high percentage of preferred responses is evidence that the conversation between them is going well.